Dural Tear, a Feared Complication of Spine Surgery - Samir Khan Kabir; Ihsan Ullah; Ubaid Ullah Khan; Muhammad Zahid Khan; Homaira Iqbal Khan (Gandhara University, 2023)
OBJECTIVES To investigate the incidence, risk factors and clinical presentation of complications in patients undergoing spinal surgery with and without Dural Tear. METHODOLOGY A one-year prospective case-control study was conducted in the department of orthopaedics and spinal surgery at the Hayatabad Medical Complex (HMC) and Rahman Medical and surgical centre Dagger Buner. The spine surgeon used a discrete surgical approach. The questionnaire was used to collect patient demographic data, surgical information, and data on perioperative and postoperative complications. SPSS version 21.0 statistical software was used for all statistical analyses. RESULTS Dural tears were observed in 3.4% of the patients, among whom 20% experienced a Dural leak. After controlling for potentially confounding variables of age, sex, primary disease, and type of procedure, the surgery-related complications that were more likely to occur in the Dural Tear group than in the non-TD group were surgical site complications OR 2.69 and postoperative neurological defect O 3.28. The proportion of postoperative delirium OR 3.22 was significantly high in the Dural Tear group as perioperative complications CONCLUSION A higher proportion of surgical site infections, postoperative neurological defects and delirium in the Dural Tear group are due to direct complications, such as Dural leakage.